564 Late Presentation of Colorectal Neuroendocrine Neoplasia Is Associated with a Poor Prognosis. (19th August 2022) - Goan, R; Camilleri-Brennan, J
Abstract: Introduction: Although neuroendocrine neoplasms (NENs) arising from the colon and rectum are generally slow growing and present early, a minority demonstrate aggressive growth and present late with metastatic disease. The aim of this study is to analyse the clinical presentation, management and prognosis of patients presenting with advanced colorectal NENs. Method: Data were collected from dedicated databases on patients with colorectal NENs who presented to our hospital between January 2015 and February 2021. Patients who presented with appendiceal NENs were excluded. Results: 13 patients with colorectal NENs were identified, of whom 3 patients (23%) had advanced disease at diagnosis. These 3 patients, 2 males (78 and 82 years old) and 1 female (71 years old), presented with weight loss, anorexia and altered bowel habit, with one patient also having rectal bleeding. The site of the primary was in the rectum (2 patients) and in the sigmoid colon (1 patient), the histology being poorly differentiated neuroendocrine carcinoma. All 3 patients had liver metastases at presentation, with 2 having lung and lymph node metastases as well. Due to their advanced disease, these patients' treatment was carried out with palliative intent. All three patients passed away within a year of diagnosis. Conclusion: Poorly differentiated colorectal NENs with distant metastases were associated with a poor prognosis. Management involves a multidisciplinary team. The use of somatostatin analogue therapy and palliative chemotherapy are options for symptom control.